Resource partitioning by top predatory teleosts in eastern Cape coastal waters (South Africa) - Smale, Malcolm J (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1984)
A detailed feeding study of eleven inshore top predatory teleosts in the eastern Cape is presented. Material collected largely from line-caught fish was augmented by spearfishing. The predators were grouped according to habitat: pelagic, soft-sediment demersal and reef species. Pelagic fish examined were Lichia amia, Pomatomus saltatrix, Seriola lalandi, Atractoscion aequidens, Katsuwonus pelamis and Thunnus albacares. Stomach content analyses revealed that their prey varied according to size and between species. In coastal areas important prey species were Sardinops ocellata, Etrumeus teres, Engraulis capensis and Loligo reynaudi. The use of fish otoliths and squid beaks allowed accurate identification of the prey and their measurement provided details of their size composition. This has provided greater insight into the distribution of prey species and their importance in food webs. The principal large predator of shallow coastal soft substrates is Argyrosomus hololepidotus, which takes pelagic and demersal prey. Important prey of small specimens are mysids, whereas fish and squid become more important in the diet of larger specimens (>300 mm). Fish prey include Sardinops ocellata, Engraulis capensis, Pomadasys olivaceum and A. hololepidotus. Loligo reynaudi is the dominant cephalopod prey. Selectivity of A. hololepidotus was investigated. Prey were compared to catches made during a small-mesh trawl survey. The absence of certain species from the diet suggests that they avoid predation, possibly by outswimming A. hololepidotus (e.g. P. saltatrix) while large Galeichthys feliceps are rare in the diet, probably because of their formidable spines. Flatfishes, P. olivaceum, juvenile G. feliceps and small A. hololepidotus appear to be preferred food items. The depth distribution of predators and prey is described, and it appears that the distribution of predators may be influenced by their prey. Top predatory teleosts inhabiting coastal reefs are Cheimerius nufar, Petrus rupestris, Polysteganus praeorbitalis and Epinephelus guaza. Diet changes with size and locality but comprises small reef fishes for most of the sparids. C. nufar takes pelagic fish and squid more than the other predators while P. rupestris and P. praeorbitalis prey on cheilodactylids, clinids and other reef associated prey predominantly. E. guaza takes principally crabs and octopods. Classification and ordination analyses of the prey taken illustrated the inter-relationships of predators, which change with increasing size. The pelagic predators are most similar to each other and A. hololepidotus is closer to this group than to reef predators. The reef predators are less similar to each other, although this group as a whole is segregated from pelagic predators. Exceptions to this are large C. nufar and large P. praeorbitalis, which fall into the pelagic predator group, as they took pelagic prey to a large extent. These results are discussed and the patterns shown are compared to other studies and current resource partitioning theory. Two food webs are provided for the coastal waters of the eastern Cape. The pelagic food web has clupeids, engraulids and L. reynaudi as principal components. The reef system is more complex and the Clinidae, Cheilodactylidae and Octopus spp. are important. The use of food webs in management and in providing a framework for testing theoretical models is shown to be important. Research needs are identified and include more detailed work on the basic biology and ecology of the top predators and their prey.
Keywords: Osteichthyes -- Nutrition; Osteichthyes -- Behavior